2021
DOI: 10.1111/ced.14749
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability profile of topical cannabidiol and palmitoylethanolamide: a compilation of single‐centre randomized evaluator‐blinded clinical and in vitro studies in normal skin

Abstract: Background. An increasing number of studies have investigated the adverse effect profile of oral cannabinoids; however, few studies have provided sufficient data on the tolerability of topical cannabinoids in human participants. Aim. To assess the tolerability profile of several commercial topical formulations containing cannabidiol (CBD) and palmitoylethanolamide (PEA) on the skin of healthy human participants. Methods. Three human clinical trials and one in vitro study were conducted. The potential for skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, given the various formulations that are in the market and the difficulty in regulating topical cannabinoids, these results are likely not generalizable to all cannabinoid products. 55 Further research is needed to understand the full spectrum of side effects of topical cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the various formulations that are in the market and the difficulty in regulating topical cannabinoids, these results are likely not generalizable to all cannabinoid products. 55 Further research is needed to understand the full spectrum of side effects of topical cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…The use of oil contributes to the reduction of analgesic pharmacotherapy. Possibility: using preparations on skin exposed to solar radiation [124] Despite Despite the similarities of various phytocannabinoids in their biological and biomedical effects, in addition to the extensively researched effects of CBD, recent years have brought new detailed data on other components of Cannabis sativa, including THC and CBG. CBG, with a broad spectrum of biological effects on skin cells in vitro, including antioxidant, anti-inflammatory, anti-acne and anti-aging properties, has also been shown in clinical trials to be both safe and effective in maintaining skin health, including reducing redness [52,121].…”
Section: Clinical Studies On the Effect Of Phytocannabinoids On Skin ...mentioning
confidence: 99%
“…Both the individual components, mainly phytocannabinoids, and Cannabis sativa extracts have been intensively studied in recent years in terms of their biological effects, especially those that protect healthy skin and heal the affected skin ( Table 3 ) [ 52 , 109 , 121 , 122 , 123 , 124 ]. However, despite the demonstrated wide range of biological properties, there is very little evidence based on clinical trials indicating the possibility of using specific preparations containing phytocannabinoids in medical practice.…”
Section: Clinical Studies On the Effect Of Phytocannabinoids On Skin ...mentioning
confidence: 99%
“…With the topical application of CBD, previous studies have not reported serious adverse events. Minorities experience minor adverse events, including erythema, skin irritation or pain, changes in hair or skin color, somnolence, and diarrhea [31,32,[61][62][63][64][65][66].…”
Section: Safety Of Cannabidiol (Cbd)mentioning
confidence: 99%